PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KEPALA BERNOMOR UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII4 SMP NEGERI 14 PEKANBARU - Wihasty Anggraini Anggraini; Zulkarnain '; Rini Dian Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Absract: This research aims to improve the learning process and improve learning result in mathematics at SMP Negeri 14 Pekanbaru by applying the model of Cooperative Learning Numbered Head Techniques. Subjects were class VII4 students who have academic ability is heterogeneous. This research is a class action research by two cycles. Each cycle has four phases, they were planning, implementation, observation and reflection. Research instrument which consists of learning tools, which are Syllabus, Learning Implementation Plans, Student Worksheet and Number Head Questions. The data analysis technique utilized comsist of descriptive data analysis technique which is divided into qualitative and quantitative data analysis technique. The result from this research shows the activity of the teacher and student had performed well after has been made. An increase in the number of students who received grades of 20 and 30 as many as 17 students on first cycle and 23 students on second cycle. That is also an increase in the number of students who achieve at KKM end of UH each cycle compared to the number of students who achieve a score of KKM on the base. Starting from 35.71% increase to 60.71% and increased to 68.14%. The development of the results of this research indicate that the application of the Cooperative Learning Numbered Heads Techniques can improve the learning process and improve learning results class VII4 junior high school math class students Negeri 14 Pekanbaru in the academic year 2013/2014. Keywords: Mathematics Learning Result, Learning Process, Cooperative Learning, Numbered Head, Classroom Action Research